2022
DOI: 10.3390/diagnostics12071547
|View full text |Cite
|
Sign up to set email alerts
|

The Matrix Effect in the RT-PCR Detection of SARS-CoV-2 Using Saliva without RNA Extraction

Abstract: The present work focuses on the detection of SARS-CoV-2 in saliva, contributing to understanding the inhibition effect of the matrix and its influence on the results. Detection of viral genes ORF1ab, N, and E was performed by RT-PCR using saliva directly in the reaction without RNA extraction. Different amounts of saliva were spiked with increasing amounts of viral RNA from COVID-19 patients and subjected to RT-PCR detection. In parallel, 64 saliva samples from confirmed COVID-19 patients were used in two diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…As saliva is easy to collect from a large number of people, pooling strategies are thus a natural extension to surveillance programs 17 . While pooling saliva does impact assay sensitivity and potentially decrease virus detection, as also observed by others 14 , 18 20 , we found that the actual impact appears to be minimal, likely due to the dilution of possible contaminants in certain saliva samples that can have an inhibitory effect on the PCR reaction 21 .…”
Section: Discussionsupporting
confidence: 76%
“…As saliva is easy to collect from a large number of people, pooling strategies are thus a natural extension to surveillance programs 17 . While pooling saliva does impact assay sensitivity and potentially decrease virus detection, as also observed by others 14 , 18 20 , we found that the actual impact appears to be minimal, likely due to the dilution of possible contaminants in certain saliva samples that can have an inhibitory effect on the PCR reaction 21 .…”
Section: Discussionsupporting
confidence: 76%
“…Positive saliva and negative nasopharyngeal aspirate have also been observed in the detection of other respiratory viruses [ 51 ]. In addition, high between-person variability and false negative rates have been obtained with minimally processed saliva [ 56 , 57 ], highlighting the need to optimize collection and processing before saliva could be applied as a standardized specimen for nucleic acid testing and large-scale screening of viral infections.…”
Section: Discussionmentioning
confidence: 99%
“…First, the saliva collection and processing methods have varied among different studies, which might directly influence the testing results. Although several studies have shown that SARS-CoV-2 RNA could be detected in unprocessed saliva [ 64 , 65 ], other studies found a high false negative rate and between-person variability using minimally processed saliva [ 56 , 57 ]. In addition, the types of saliva (unstimulated, stimulated, unforced saliva, and forced deep throat saliva), the part of saliva (cell or cell-free), and behaviors before testing (eating and mouth washing) also interfere with SARS-CoV-2 detection [ 66 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, saliva as specimen poses challenges for sampling handling and processing in laboratories due to its inherent properties such as viscosity and heterogeneity [10]. Furthermore, saliva contains PCR inhibitors which may affect the effectiveness for PCR-based diagnostics especially if saliva is directly used in the PCR reaction [11].…”
Section: Introductionmentioning
confidence: 99%